2009
DOI: 10.2106/jbjs.g.01193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Single Infusion of Zoledronic Acid on Early Implant Migration in Total Hip Arthroplasty

Abstract: A single infusion of zoledronic acid shows promise in improving initial fixation of a cementless implant, which may improve the clinical outcome of total hip arthroplasty in patients with osteonecrosis of the femoral head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 29 publications
2
84
0
1
Order By: Relevance
“…Data from new investigations emphasise that the acetabular component may be primarily exposed to biological factors while the fixation of the femoral component may be substantially affected by non-biological factors [15]. The influence of these non-biological factors such as body weight, BMI and height upon the migration behaviour of implants is still unresolved in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Data from new investigations emphasise that the acetabular component may be primarily exposed to biological factors while the fixation of the femoral component may be substantially affected by non-biological factors [15]. The influence of these non-biological factors such as body weight, BMI and height upon the migration behaviour of implants is still unresolved in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies of large patient cohorts have shown that chronic systemic bisphosphonate therapy can offer benefits to patients undergoing total joint arthroplasty, including reduction of periprosthetic bone loss [2,3], reduction of implant migration [7], and reduction in revision rate [20]. However, these benefits need to be balanced against the risk of adverse events related to chronic bisphosphonate therapy [17], including atypical femur fracture.…”
Section: Discussionmentioning
confidence: 99%
“…As such, they have potential for use with orthopaedic devices designed for total joint replacement. Several clinical studies of large patient cohorts have shown that systemic delivery of bisphosphonates can reduce revision rates for total joint replacement implant loosening [2,3,7,20], but systemic treatment exposes the entire skeleton to the drug, thereby subjecting patients to the associated risks of side effects or adverse events such as nausea, vomiting, epigastric pain, and dypsepsia [17]. This potentially can be avoided by locally releasing the bisphosphonate directly from the implant to the surrounding bone as seen in our previous radioactive studies showing insignificant levels of the drug outside the direct periimplant region exposed to the bisphosphonate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Without data showing important effects on clinical outcome, a potential beneficial effect of bisphosphonates on periprosthetic bone after TJA was viewed with reservation [45]. From 2006 to the present, multiple studies established efficacy of oral alendronate on bone mineral density around the knee and the hip [1,15,18,32,47]. These studies generally related to loss of bone resulting from mechanics and not osteolysis.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%